Genetic Diversity of Introduced (Pomacea canaliculata) and Native (PILA) Apple Snails in Thailand Revealed by Randomly Amplified Polymorphic DNA (RAPD) Analysis - B. Thaewnon-ngiw; S. Klinbunga; K. Phanwichien; N. Sangduen; N. Lauhachinda; P. Menasveta (ASEAN Journal on Science and Technology for Development, 2003)
Genetic diversity of the introduced golden apple snail, Pomacea canaliculata (Lamarck, 1822) and four native apple snails; Pila ampullacea (Linneaus, 1758), P. angelica (Annandale, 1920), P. pesmei (Morelet, 1889) and P. polita (Deshayes, 1830) in Thailand were studied by RAPD analysis. Two hundred and two polymorphic fragments (180-1500 bp in length) were generated across overall investigated samples (N = 254) using three informative primers (OPA07, OPB10 and UBC122). The percentages of polymorphic bands were 98.86%, 94.56%, 90.91%, 96.94% and 95.51% for Pomacea canaliculata, P. ampullacea, P. angelica, P. pesmei and P. polita, respectively. This indicated high genetic polymorphism of these taxa. A neighbor-joining tree between pairs of geographic samples within Pomacea canaliculata suggested a lack of phylogeography in this species. Moreover, candidate species-specific RAPD markers (pKUSCARPILA-F/R) found in Pomacea canaliculata (340 bp, OPB10), P. ampullcea (640 bp, OPA07), P. angelica (380 bp, UBC122) and Pila snails (430 bp, OPA07) were cloned and sequenced. Locus-specific primers were designed and tested against the target and nontarget species. A 259 bp SCAR marker was found in 95.0% of Pila apple snails (N = 163) but not in Pomacea canaliculata (N = 30). Therefore, this SCAR marker could be used in coupling with a Pomacea canaliculata-specific RAPD marker to unambiguously differentiate the introduced and native apple snails in Thailand.